‫المسؤوليــة‬‫الدوليـــة‬ ‫عن‬ ‫انتهـــاك‬ ‫المـــوارد‬ ‫المائيـــة‬ ‫وقــت‬ ‫النـــزاعات‬ ‫المسلحـــة‬ - ‫د‪.‬مصطفي‬ ‫عثمان‬ ‫عبدالله‬ ‫عبد‬ ‫الكريم‬; ‫أ‪.‬‬ ‫حامد‬ ‫سليمان‬ ‫حموده‬ ‫الزافي‬ (White Nile Journal for Studies and Research, 2018)
The study, entitled 'International Responsibility for the Violation of Water Resources in Times of Armed Conflict, aimed at clarifying the international criminal responsibility of moral and natural persons, the impact of the attack on water resources, its origin and the consequent responsibility. Is a violation of the water resources and their establishment by the armed forces of the parties to the conflict, and does this entail responsibility for the Head of State or military commanders? The study used the inductive analytical method, and the most important results were in: That the crimes committed by heads of State and leaders against water resources and their origin at the time of armed conflict have become a matter of internationally recognized principles, immunity cannot be invoked, and those under their responsibility are not subject to liability and punishment based on obedience to orders and instructions. The recommendations were: the necessity of prosecuting the perpetrators of crimes against water resources and their origin and trial before competent courts regionally and internationally, and the search end by table of sources and reference.